Clinical Pharmacogenetics Implementation Consortium Guidelines for Human Leukocyte Antigen‐B Genotype and Allopurinol Dosing. Issue 2 (17th October 2012) - Hershfield, M S; Callaghan, J T; Tassaneeyakul, W; Mushiroda, T; Thorn, C F; Klein, T E; Lee, M T M
<x xml:space="preserve">Abstract</x> Allopurinol is the most commonly used drug for the treatment of hyperuricemia and gout. However, allopurinol is also one of the most common causes of severe cutaneous adverse reactions (SCARs), which include drug hypersensitivity syndrome, Stevens–Johnson syndrome, and toxic epidermal necrolysis. A variant allele of the human leukocyte antigen (HLA)‐B, HLA‐B*58:01, associates strongly with allopurinol‐induced SCAR. We have summarized the evidence from the published literature and developed peer‐reviewed guidelines for allopurinol use based on HLA‐B genotype. Clinical Pharmacology & Therapeutics (2013); 93 2, 153–158. doi:10.1038/clpt.2012.209